Dampak Sertifikasi terhadap Kinerja Usaha Mikro dan Kecil Indonesia : Analisis Propensity Score Matching - Putra Irwandi; Novita, Ninda (RUBINSTEIN, 2026)
Certification is a strategic tool for improving business performance, competitiveness, and expanding market access. Although numerous studies on certification have been conducted, these studies are limited to specific sectors and regions. Furthermore, the types of certification examined typically focus on a single specific certification. No previous study has focused on the impact of certification on business performance using nationwide data and a quasi-experimental approach via PSM while covering all types of certification. This study aims to analyze the impact of certification on the performance of Micro and Small Enterprises in Indonesia using Propensity Score Matching. The research method employs a quantitative causal approach, with data sourced from the 2019 Micro and Small Enterprise Survey conducted by the Central Statistics Agency, covering a total of 52,551 enterprises. Data analysis was conducted using Propensity Score Matching with the assistance of STATA 17 software. The business performance variables measured were Turnover and Profit. The results indicate that certification has a positive and significant impact on business performance, with a T-statistic significance value of 2.55 for the turnover variable and 1.81 for the profit variable. The ATT values obtained for the revenue variable are 34.19 and for the profit variable are 7.89, which means that certified businesses saw an increase in revenue of Rp 34.19 million and an increase in profit of Rp 7.89 million. The theoretical implication is the need to expand and provide guidance on obtaining certification, as well as to facilitate access so that certification is distributed more evenly and is accessible to all business actors. The conclusion of this study is that the implementation of certification is important for Micro and Small Enterprises and improves business performance, specifically in terms of turnover and profit.